BVGer F-4439/2025 vom 15. Mai 2025 - Bundesverwaltungsgericht (2025)
Rechtsverzögerung/Rechtsverweigerung | Rechtsverzögerung/Rechtsverweigerung; Verfügung des SEM vom 15. Mai 2025. Entscheid angefochten beim BGer.